Dispersible oxygen microsensors map oxygen gradients in three-dimensional cell cultures. (14th August 2017) - Lesher-Pérez, Sasha Cai; Kim, Ge-Ah; Kuo, Chuan-hsien; Leung, Brendan M.; Mong, Sanda; Kojima, Taisuke; Moraes, Christopher; Thouless, M. D.; Luker, Gary D.; Takayama, Shuichi
Abstract : Oxygen measurements in different microtissue culture environments were accomplished with the use of phase fluorimetry on dispersible oxygen microsensors. Abstract : Phase fluorimetry, unlike the more commonly used intensity-based measurement, is not affected by differences in light paths from culture vessels or by optical attenuation through dense 3D cell cultures and hydrogels thereby minimizing dependence on signal intensity for accurate measurements. This work describes the use of phase fluorimetry on oxygen-sensor microbeads to perform oxygen measurements in different microtissue culture environments. In one example, cell spheroids were observed to deplete oxygen from the cell-culture medium filling the bottom of conventional microwells within minutes, whereas oxygen concentrations remained close to ambient levels for several days in hanging-drop cultures. By dispersing multiple oxygen microsensors in cell-laden hydrogels, we also mapped cell-generated oxygen gradients. The spatial oxygen mapping was sufficiently precise to enable the use of computational models of oxygen diffusion and uptake to give estimates of the cellular oxygen uptake rate and the half-saturation constant. The results show the importance of integrated design and analysis of 3D cell cultures from both biomaterial and oxygen supply aspects. While this paper specifically tests spheroids and cell-laden gel cultures, the described methods should be useful for measuring pericellular oxygen concentrations in a variety of biomaterials and culture formats.